Effect of water hyacinth root extract on arsenic level in different organs of arsenic-treated rat - Shaheen Lipika Quayum (Bangladesh Pharmacological Society, 2007)
The present study investigated whether the administration of the ethanol extract of water hyacinth (Eichhornia crassipes) ameliorates arsenic from arsenic-treated rats. To induce arsenic accumulation in different organs, arsenic trioxide was administered orally by gavage at a dose of 500 µg/rat/day for 7 days. In search of an effective therapeutic agent to counteract arsenic accumulation and arsenic-induced oxidative stress, different concentrations of ethanol extract of root of water hyacinth (100%, 75%, 50%, and 25%) were administered by intraperitoneal injection for last two days which significantly reduced the arsenic accumulation in liver, spleen, kidney, intestine, lungs and skin. Besides, it reduced the oxidative stress caused by arsenic, which was evident by decreased levels of malondialdehyde (MDA) in the above organs. Treatment with either extract 50% or with alpha-tocopherol was applied singly and in combination to find out result for comparison of effectiveness on arsenic removal. But the reduction of arsenic and MDA was not dose dependent and not parallel. Water hyacinth, at the dose of 50% extract was observed to be most effective.